2019
DOI: 10.1111/bcp.13955
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase‐4 inhibitors lower the risk of autoimmune disease in patients with type 2 diabetes mellitus: A nationwide population‐based cohort study

Abstract: Aims: To evaluate the real-world effect of dipeptidyl peptidase-4 inhibitor (DPP4i) on the incidence of autoimmune diseases (AD), including rheumatoid arthritis (RA), inflammatory bowel diseases, multiple sclerosis and systemic lupus erythematosus. Methods: We identified new users of DPP4i (n = 497 619) or non-DPP4i (n = 643 165) oral combination therapy between 1 January 2011 and 30 June 2015 among patients with type 2 diabetes mellitus in the Korean national health insurance claims database. Patients were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…In addition, another population-based study conducted by Kim et al found that DPP-4 inhibitors may reduce the risk of RA and composite autoimmune disease [36]. Another population-based cohort study using Korean National Health Insurance Claims Database found that the risk of incident RA and composite AD was decreased for DPP4i initiators compared with non-DPP4i initiators, which was consistent with our findings [37]. Our cohort study, which had a follow-up period of 5 years between January 2009 and December 2013, is distinct because we included large Asian population (387,099 in DPP-4i group vs. 387,099 in DPP-4i-naive group).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, another population-based study conducted by Kim et al found that DPP-4 inhibitors may reduce the risk of RA and composite autoimmune disease [36]. Another population-based cohort study using Korean National Health Insurance Claims Database found that the risk of incident RA and composite AD was decreased for DPP4i initiators compared with non-DPP4i initiators, which was consistent with our findings [37]. Our cohort study, which had a follow-up period of 5 years between January 2009 and December 2013, is distinct because we included large Asian population (387,099 in DPP-4i group vs. 387,099 in DPP-4i-naive group).…”
Section: Discussionsupporting
confidence: 91%
“…In a large cohort of diabetic patients, those initiating DPP4i combination therapy appeared to have a decreased risk of autoimmune diseases including RA (hazard ratio 0.66) compared with those initiating non-DPP4i combination therapy (Kim et al, 2015). Similar result was found in a large population-based cohort study conducted by Seong (Seong, Yee, & Gwak, 2019). However, using the United Kingdom CPRD, Douros conducted a cohort study among 144,603 patients with T2DM initiating OADs between 2007 and 2016, and found that use of DPP4is is not associated with any increased/decreased risk of incident RA .…”
Section: Dpp4/cd26 Inhibition On Rasupporting
confidence: 75%
“…Decreased risk in T2DM patients (Kim et al, 2015;Seong et al, 2019) No association in T2DM patients Increased disease severity in animal model (Busso et al, 2005;Ospelt et al, 2010) Allograft rejection…”
Section: Ramentioning
confidence: 99%
“…For example, pharmacological inhibition of DPP4 decreased incidence, onset of symptoms and overall disease severity in the experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis 23 . This is consistent with human data, where inhibitors of DPP4/CD26 suppress activation of Myelin basic protein (MBP)‐specific CD4+ T‐cell clones, 24 and with observations from population‐based cohort studies where DPP4i usage was associated with a 30% lower risk of incident autoimmune diseases 25,26 . Interestingly, in an experimental model of acute respiratory distress syndrome (ARDS), which represent the main death cause of SARS‐CoV‐2 infected patients, DPP4 inhibition by sitagliptin alleviated histological findings of lung injury by inhibiting proinflammatory cytokines IL‐1β, TNFα, and IL‐6 27 .…”
supporting
confidence: 79%